2017
DOI: 10.1103/physrevb.95.045111
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-protected topological entanglement

Abstract: We propose an order parameter for the Symmetry-Protected Topological (SPT) phases which are protected by Abelian on-site symmetries. This order parameter, called the SPT-entanglement, is defined as the entanglement between A and B, two distant regions of the system, given that the total charge (associated with the symmetry) in a third region C is measured and known, where C is a connected region surrounded by A, B and the boundaries of the system. In the case of 1-dimensional systems we prove that in the limit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…Finally, while we mainly have studied what is usually referred to as 'long-range entangled' phases, an algebraic approach to symmetry protected phases appears to be reasonable; as a toy model one can consider the Kitaev wire, and divide the system into three parts, as we did in the example of the Fibonacci chain. We conjecture that this can be related to a notion of entanglement entropy for symmetry protected phases, see [58].…”
Section: Summary and Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, while we mainly have studied what is usually referred to as 'long-range entangled' phases, an algebraic approach to symmetry protected phases appears to be reasonable; as a toy model one can consider the Kitaev wire, and divide the system into three parts, as we did in the example of the Fibonacci chain. We conjecture that this can be related to a notion of entanglement entropy for symmetry protected phases, see [58].…”
Section: Summary and Discussionmentioning
confidence: 91%
“…Already in 1989 Longo showed that the quantum dimension d i of a representative of a superselection sector can be obtained as the index of a certain inclusion of von Neumann algebras [32]. Later in 2001 it was shown that for the class of rational conformal field theories on the circle, the total quantum dimension is equal to the index of an inclusion Ì    , very similar to the inclusion Ì   AB AB  [55], and indeed our results are partially motivated by that paper. A similar strategy can be applied to the lattice models that we are interested in.…”
Section: Total Quantum Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that the quantity called SPT entanglement, defined in [12] and shown there to label SPT states (at least for abelian groups), is an example of a measurement-based protocol similar to the ones we study.…”
mentioning
confidence: 69%